Health inequities related to vaccination: An evidence map of potentially influential factors and systematic review of interventions. Issue 29 (29th June 2021) - Gates, Allison; Rahman, Sholeh; Sim, Shannon; Pillay, Jennifer; Ismail, Shainoor J.; Tunis, Matthew C.; Keto-Lambert, Diana; Hartling, Lisa
Abstract: Introduction: The National Advisory Committee on Immunization (NACI) makes recommendations for vaccines in Canada. To inform considerations for equity when making recommendations, the NACI Secretariat developed a matrix of factors that may influence vaccine equity. To inform the matrix we mapped the evidence for P 2 ROGRESS And Other factors potentially associated with unequal levels of illness or death from vaccine-preventable diseases (VPDs) and systematically reviewed the evidence for interventions aimed at reducing inequities. Methods: In October 2019 we searched Medline, Embase, and CINAHL. Two reviewers agreed on the included studies. Our primary outcomes were VPD-related hospitalizations and deaths. Secondary outcomes were differential vaccine access, and exposure, susceptibility, severity, and consequences of VPDs. Two reviewers appraised the certainty of evidence. We mapped the evidence for P 2 ROGRESS And Other factors and summarized the findings descriptively. We summarized the interventions narratively. Results: We identified 413 studies reporting on P 2 ROGRESS And Other factors. The most commonly investigated factors included age (n = 374, 89%), pre-existing conditions (n = 179, 42%), and gender identity or sex (n = 144, 34%). We identified 2 trials investigating the effects of interventions. One (n = 1249) provided very low certainty evidence that staff vaccination policies may reduce hospitalizations and deaths from influenza among private care home residents. The other (n not reported) provided very low certainty evidence that universal vaccination by nurses in clinics may reduce hospitalizations for rotavirus gastroenteritis compared with vaccination by physicians or no intervention. Conclusions: There is a large body of studies reporting on hospitalizations and deaths from VPDs stratified by P 2 ROGRESS And Other factors. We found only two trials examining the effects of interventions on hospitalization for or mortality from VPDs. This review has been helpful to NACI and will be helpful to similar organizations aiming to systematically identify and target health inequities through the development of vaccine program recommendations.